2002
DOI: 10.1111/1467-9566.00294
|View full text |Cite
|
Sign up to set email alerts
|

Fordism in the fast food industry: pervasive management control and occupational health and safety risks for young temporary workers

Abstract: A growing body of international research points to an association between precarious employment or contingent work arrangements and a higher incidence of injury, disease and psychological distress as well as inferior knowledge/compliance with occupational health and safety (OHS) standards. Despite this, published research on the OHS problems of young workers in hospitality and other service industries largely ignores the fact that many are engaged on a temporary basis. To address this gap we surveyed 304 young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 32 publications
1
31
1
Order By: Relevance
“…As previously mentioned, teenagers are most likely to work low skilled, entry-level positions. Service-oriented jobs generally have few opportunities for meaningful individual and collective participation in organizing and controlling work (Mayhew & Quinlan, 2002). Further, across Canada, the union density rate among 15 to 24 year olds has fallen steadily in the past two decades and is currently 15% (Uppal, 2010), while the rate of unionization among temporary workers aged 15 to 17 is about 8% (Galarneau, 2005).…”
Section: Young Workers Responses To Unsafe Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, teenagers are most likely to work low skilled, entry-level positions. Service-oriented jobs generally have few opportunities for meaningful individual and collective participation in organizing and controlling work (Mayhew & Quinlan, 2002). Further, across Canada, the union density rate among 15 to 24 year olds has fallen steadily in the past two decades and is currently 15% (Uppal, 2010), while the rate of unionization among temporary workers aged 15 to 17 is about 8% (Galarneau, 2005).…”
Section: Young Workers Responses To Unsafe Workmentioning
confidence: 99%
“…Research has identified several causes of young worker injuries have been identified including short job tenures (Breslin & Smith, 2006), work pressure (Tannock, 2001), and managerial control systems (Mayhew & Quinlan, 2002) (for a review see Breslin et al, 2007a). In terms of responses to hazards, interviews with Canadian teenage workers found that making complaints about safety concerns was not prevalent (Breslin, Polzer, MacEachen, Morrongiello, & Shannon, 2007b); young males stifled speaking up, while young females attempts at speaking up were delegitimized by supervisors.…”
Section: Young Workers Responses To Unsafe Workmentioning
confidence: 99%
“…One exception was a survey of young workers in a global fast food chain in which casuals typically worked approximately 17 hours per week. 13 While most were willing to be reasonably flexible about their working hours, there was conflict between the employers' requirements and workers' preferences in relation to early shifts. Another study found that both self-employed and employee bar workers typically worked more than 49 hours per week.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently the pace of work is frantic, with pressure from supervisors and customers to work even faster. An establishment often operates with razor-thin profitability and provides negligible job security (Mayhew & Quinlan, 2002). Add to this mix of dangers and pressures the rapid turnover and lower education of staff drawn from multiple language communities and crowded into an overheated space (Blosser, 1999;Dunn, Runyon, Cohen, & Schulman, 1998;Evensen, Schulman, Runyan, Zakocs, & Dunn, 2000;Hendricks & Layne, 1999).…”
Section: Introductionmentioning
confidence: 99%